2013
DOI: 10.1111/bld.12076
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of people with learning disabilities in the criminal justice system

Abstract: Accessible Summary Many people with learning disabilities are caught up in the criminal justice system. Yet few studies have explored what this is like for them. The available research suggests that people with learning disabilities often feel alone and afraid when they are caught up in the criminal justice system. They do not understand what is happening to them, and they feel like there is no one they can turn to for support. The findings raise concerns about how people with learning disabilities are treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The process of being arrested and taken into police custody is intrinsically stressful (Newburn, 2013); someone with an existing mental disorder is likely to find it exceptionally so (HM Inspectorate of Constabulary, 2015). Vulnerable suspects have reported that they often do not understand what is happening or why, and highlight uncertainty about what to say or do when being interviewed by the police (Hyun, Hahn, & McConnell, 2014). Perhaps as a partial consequence, research has consistently shown that suspects with mental disorder are at heightened risk of falsely confessing to crimes (Kassin & Gudjonsson, 2004;Littlechild, 2001;Redlich, 2004).…”
Section: Police Custody and The Suspect With Mental Disordermentioning
confidence: 99%
“…The process of being arrested and taken into police custody is intrinsically stressful (Newburn, 2013); someone with an existing mental disorder is likely to find it exceptionally so (HM Inspectorate of Constabulary, 2015). Vulnerable suspects have reported that they often do not understand what is happening or why, and highlight uncertainty about what to say or do when being interviewed by the police (Hyun, Hahn, & McConnell, 2014). Perhaps as a partial consequence, research has consistently shown that suspects with mental disorder are at heightened risk of falsely confessing to crimes (Kassin & Gudjonsson, 2004;Littlechild, 2001;Redlich, 2004).…”
Section: Police Custody and The Suspect With Mental Disordermentioning
confidence: 99%
“…Recent research further indicates that 'mentally vulnerable' people in custody did not understand what was happening to them or why, said that they felt alone, they did not know who to turn to for support and that they were uncertain about what they should say and do (Hyun et al, 2014). Despite discussions relating to evidential requirements outlined above, the authors here proceed on the basis that there is a need for Appropriate Adult services to emotionally support people who have been identified as being 'vulnerable' throughout a difficult and stressful experience.…”
Section: 'Vulnerable Adults': Policy Contextmentioning
confidence: 99%
“…cardiovascular disease) (Dias et al 2012(Dias et al , 2013. Prisoners with ID are also at increased risk of social isolation during incarceration and confusion about their circumstances, which can lead to institutionalisation and becoming trapped in the 'revolving door of prison' through continued recidivism (Holland & Persson 2011;Hyun et al 2013).…”
Section: Introductionmentioning
confidence: 99%